A new species of Karschiola Gaede from Mozambique and Zimbabwe (Lepidoptera: Erebidae: Arctiinae) with updated information on the distribution of the genus - László, Gyula M.; Volynkin, Anton V. (Zootaxa, 2023)
The present paper provides the description of a new species of the genus Karschiola Gaede, 1926 from central Mozambique and Zimbabwe: K. ndzou sp. n. The pairwise genetic distance between the two Karschiola species is calculated and a neighbour-joining tree based on DNA barcodes of two K. holoclera and five K. ndzou sp. n. specimens is provided. The paper is illustrated with eight colour photos of adults and 18 genitalia images, a distribution map and two habitat photos.